PLS3 Mutations Cause Severe Age and Sex-Related Spinal Pathology - Mäkitie, Riikka E.; Niinimäki, Tuukka; Suo-Palosaari, Maria; Kämpe, Anders; Costantini, Alice; Toiviainen-Salo, Sanna; Niinimäki, Jaakko; Mäkitie, Outi (Frontiers in Endocrinology, 2020)
Objective: Mutations in the X-chromosomal PLS3-gene, encoding Plastin 3, lead to severe early-onset osteoporosis, suggesting a major role for PLS3 in bone metabolism. However, the consequences of abnormal PLS3 function in bone and other tissues remain incompletely characterized. This study evaluated spinal consequences of aberrant PLS3 function in patients with PLS3 mutations. Design: A cross-sectional cohort study with spinal magnetic resonance imaging of 15 PLS3 mutation-positive (age range 9–77 years) and 13 mutation-negative (9–70 years) subjects. Images were reviewed for spinal alignment, vertebral heights and morphology, intervertebral disc changes and possible endplate deterioration. Results: Vertebral changes were significantly more prevalent in the mutation-positive subjects compared with the mutation-negative subjects; they were most abundant in upper thoracic spine, and in all age groups and both sexes, although more prominent in males. Difference in anterior vertebral height reduction was most significant in T5 and T6 (p=0.046 and p=0.041, respectively). Mid-vertebral height reduction was most significant in T3 and T5 (p=0.037 and p=0.005, respectively), and, for male mutation-positive subjects only, in T4 and T6–10 (p=0.005–0.030 for each vertebra). Most of the abnormal vertebrae were biconcave in shape but thoracic kyphosis or lumbar lordosis were unchanged. Vertebral endplates were well-preserved in the mutation-positive subjects with even fewer Schmorl nodes than the mutation-negative subjects (10 vs 16). Conclusions: Compromised PLS3 function introduces severe and progressive changes to spinal structures that are present already in childhood, in both sexes and most abundant in upper thoracic spine. Cartilaginous structures are well preserved.